As origens dos Mardi Gras Indians de Nova Orleans em contexto atlântico - Brasil, Eric (Afro-Ásia, 2019)
Resenha de: DEWULF, Jeroen. From the Kingdom of Kongo to Congo Square: Kongo Dances and the Origins of the Mardi Gras Indians. Lafayette: University of Louisiana at Lafayette Press, 2017. 242p.